PEMBARUAN UI/UX ZALORA UNTUK PENINGKATAN PENGALAMAN MARKETPLACE SELLER & CUSTOMER - Susi Hartanto (Jurnal Da Moda, 2022)
To improve the shopping experience for customers, and provide better selling experience services for marketplace sellers, as of 2021-2022, Zalora updated the UI/UX on the Zalora platform and seller center. There are 8 additional features that are considered to help sellers and customers interact better: 1) Seller Rating Information; 2) There are new payment methods, especially pay later; 3) Payment method improvement; 4) Account verification via email and cellphone number; 5) Address input via geocoding; 6) Voucher in PDV; 7) Zalora Interactive Store; 8) Loyalty Programs; and 9) Z-Live. Key words : UI, UX, Zalora, Marketplace, Seller, Customer Untuk meningkatkan pengalaman berbelanja bagi pelanggan, dan memberikan servis pengalaman berjualan yang lebih baik bagi penjual marketplace, per 2021-2022, Zalora memperbarui UI/UX pada platform Zalora dan seller center. Adapun 8 fitur tambahan yang dinilai membantu para penjual dan pelanggan berinteraksi lebih baik: 1) Informasi Rating Penjual; 2) Ada metode pembayaran baru, terutama paylater; 3) Perbaikan Metode Pembayaran; 4) Verifikasi akun via email dan nomor hp; 5) Input alamat melalui geokoding; 6) Voucher in PDV; 7) Zalora Interactive Store; 8) Program Loyalti; dan 9) Z-Live. Kata Kunci: UI, UX, Zalora, Marketplace, penjual, pelanggan